Association of severe lymphopenia and disease progression in unresectable locally advanced non-small cell lung cancer treated with definitive chemoradiation and immunotherapy. (April 2021) - Friedes, Cole; Chakrabarti, Turja; Olson, Sarah; Prichett, Laura; Brahmer, Julie R.; Forde, Patrick M.; Voong, Ranh K.; Marrone, Kristen A.; Lam, Vincent K.; Hann, Christine L.; Broderick, Stephen R.; Battafarano, Richard J.; et al.
Highlights: 78 patients with LA-NSCLC were assessed for severe lymphopenia at the initiation of ICIs. After CRT, lymphocyte counts significantly decreased and 18 patients had lymphopenia. Patients with severe lymphopenia experienced worse PFS than those without lymphopenia. On MV modeling, lymphopenia remained a predictor of worse PFS. Abstract: Background: Definitive chemoradiation with consolidative immunotherapy offers the best chance for cure in patients with unresectable, locally advanced non-small cell lung cancer (NSCLC). However, treatment-related lymphopenia (TRL) may negatively impact outcomes. Methods: Patients definitively treated with chemoradiation and immunotherapy from 2015 to 2019 at a single tertiary academic center were identified. Severe lymphopenia was defined as < 0.5 × 10 9 cells/L. Progression-free survival (PFS) was calculated by Kaplan Meier methodology. Univariate and multivariate Cox Proportional Hazard modeling was used to correlate clinical variables with disease outcome. Immune-related adverse events (irAEs) were assessed according to CTCAE version 5.0 criteria. Results: Seventy-eight patients were included in the final cohort. The median age was 66 years (IQR: 58−73), 55 % were males, and 88 % had a KPS of >70. At baseline, 90 % (n = 70/78) of patients had a normal ALC and one patient had severe lymphopenia. After chemoradiation, the median ALC decreased from 1.52 × 10 9 cells/L (IQR: 1.23–1.98) to 0.72 × 10 9 cells/L (IQR: 0.52−0.94) (p < 0.001), 22 % (n = 17/78) of patients had a normal ALC, and 23 % (n = 18/78) of patients developed severe lymphopenia. Patients who initiated consolidative immunotherapy with severe lymphopenia had worse PFS than those who did not (median 217 days [IQR: 120–434] vs. 570 days [IQR: 401-NR], p < 0.001). On multivariate modeling, severe lymphopenia at the time of immunotherapy initiation remained an independent predictor of worse PFS (HR 4.90, p < 0.001). Conclusions: This is the first report to associate severe TRL with disease progression in patients with locally advanced NSCLC receiving consolidative immunotherapy. Factors associated with development of lymphopenia and strategies to mitigate lymphopenic effects should be considered.